Structure-based analysis of five novel disease-causing mutations in 21-hydroxylase-deficient patients - Minutolo, Carolina (2011)
Fil: Minutolo, Carolina. ANLIS Dr.C.G.Malbrán. Centro Nacional de Genética Médica; Argentina.